Evaluation and optimization of electrocoagulation for treating Kraft paper mill wastewater. Issue 1 (February 2020) - Wagle, Dipendra; Lin, Che-Jen; Nawaz, Tabish; Shipley, Heather J.
Graphical abstract: Abstract: The performance of electrocoagulation (EC) using iron as sacrificial electrode was investigated at low current densities (0.6–1.9 mA/cm 2 ) for treating a waste stream from a Kraft paper mill. A multi-level factorial design of experiments and response surface methodology (RSM) were applied to quantify the effects of current density and reaction time on the removal efficiency of color, COD, BOD5, tannin/lignin as well as on the enhancement of biodegradability index (BI). Increasing current density or reaction time significantly improve the treatment performance. An antagonistic effect of the two studied factors was identified, indicating that simultaneously increasing current density and reaction time does not yield added improvement in treatment performance. An RSM was developed to predict the optimum current density and reaction time within the experimental data range of this study. It was found that an optimized treatment combination exists at relatively low current density and reaction time. The optimum value for maximum pollutants removal was ∼1.5 mA/cm 2 and ∼25 min. Under the optimum condition, the removals of tannin/lignin and color were >70 % and >95 %, and BI was increased to 0.41 BOD5 /COD. Current density is the dominant factor for energy consumption and operating cost compared to reaction time and electrode consumption. This study demonstrated that EC can be operated at low current density to remove the bio-refractory organics effectively and increase the biodegradability index to the level suitable to biological treatment at low operating costs.